GAMBLING IN THE DIGITAL AGE: A SYSTEMATIC REVIEW OF THE LITERATURE ON THE PHENOMENON OF ONLINE GAMBLING - Loso Judijanto; Tehedi Tehedi (CV. Adiba Aisha Amira, 2024)
The development of digital technology has brought significant changes in various aspects of life, including the gambling industry. The phenomenon of online gambling has become a global concern due to its accessibility and potential impact. The research method used was literature review. The results of the review showed that online gambling has unique characteristics that distinguish it from conventional gambling, including accessibility, anonymity, and a wider variety of games. Research also revealed an increased risk of addiction and mental health problems related to online gambling. Therefore, a comprehensive and collaborative approach involving various stakeholders is needed to address the complexity of online gambling problems in the digital era.